2022
DOI: 10.3389/fimmu.2022.1021351
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological decrements in midlife type-2 diabetes are not associated with peripheral NLRP3 inflammasome responsiveness

Abstract: Midlife Type 2 Diabetes Mellitus (T2DM) is associated with an increased risk of Alzheimer Disease (AD) in later life, with altered inflammatory responses postulated as key pathological drivers. Previous studies have demonstrated increased responsiveness to NLR family pyrin domain containing 3 (NLRP3) inflammasome agonists, both in individuals with untreated T2DM in addition to those with established AD. We hypothesised that peripheral NLRP3 inflammasome responses may be altered during the early stages of T2DM-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 41 publications
(42 reference statements)
0
1
1
Order By: Relevance
“…In contrast to other studies in which the male subjects were ranged between 42.9 and 65.0 % [ [21] , [22] , [23] ], the proportion of male and female subjects in our study was relatively similar (49.6 vs. 50.4 %) with the median age, duration of T2DM, and HbA1c were 53 (40–59) years, 7 (0–30) years and 7.6 (5.0–15.5)%, respectively. Our findings were quite similar to that of Dyer et al (2022) [ 23 ] with mean HbA1c of 7.7 %, but higher than what was reported by Cetinus et al (2005) [ 24 ] with mean HbA1c of 7.14 (1.64)%. However, higher proportion of subjects in our study was still with uncontrolled glycaemia (68.4 %), especially among female (73.1 %).…”
Section: Discussioncontrasting
confidence: 59%
“…In contrast to other studies in which the male subjects were ranged between 42.9 and 65.0 % [ [21] , [22] , [23] ], the proportion of male and female subjects in our study was relatively similar (49.6 vs. 50.4 %) with the median age, duration of T2DM, and HbA1c were 53 (40–59) years, 7 (0–30) years and 7.6 (5.0–15.5)%, respectively. Our findings were quite similar to that of Dyer et al (2022) [ 23 ] with mean HbA1c of 7.7 %, but higher than what was reported by Cetinus et al (2005) [ 24 ] with mean HbA1c of 7.14 (1.64)%. However, higher proportion of subjects in our study was still with uncontrolled glycaemia (68.4 %), especially among female (73.1 %).…”
Section: Discussioncontrasting
confidence: 59%
“…Although the mentioned studies did not analyze the circulating levels of NLRP3, they still supported the results of our study, proposing a possible role of the NLRP3 inflammasome in T2DM. On the contrary, Dyer et al analyzed NLRP3 gene expression in PBMCs in midlife T2DM and HC and found no significant differences [37]. A possible explanation for these contradicting results is that they only included T2DM patients with no further complications.…”
Section: Discussionmentioning
confidence: 95%